2022
DOI: 10.1021/acssuschemeng.1c05721
|View full text |Cite
|
Sign up to set email alerts
|

Metal Reclamation from Spent Lithium-Ion Battery Cathode Materials: Directional Conversion of Metals Based on Hydrogen Reduction

Abstract: The vast amount of spent lithium-ion batteries (LIBs), after exhausting their useful life, necessitates comprehensive recycling for metal reclamation. This paper proposed using hydrogen as a green reductant to reduce the cathode materials of spent LIBs, followed by wet magnetic separation. The inspiration behind this is to realize pollution-free and highly efficient separation of high-value metals from LIB cathode materials by utilizing hydrogen reduction to attain directional conversion of metals based on wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For each batch of activation experiments, specific proportions of the cathode material and spent graphite, and zirconia balls (3 mm diameter) were placed in the zirconia pot. The effects on the Li leaching efficiency of the cathode materials to spent graphite mass ratios (6,12,18,24,30,36,42, and 48 g g −1 ), ball-to-powder mass ratios (5,10,15,20, and 25 g g −1 ), mill rotation speeds (200, 400, 600, and 800 rpm), and rotation times (2, 4, 6, and 8 h) were investigated systematically. To prevent the equipment from overheating, the ball mill was operated continuously for 10 min with 10 min intervals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each batch of activation experiments, specific proportions of the cathode material and spent graphite, and zirconia balls (3 mm diameter) were placed in the zirconia pot. The effects on the Li leaching efficiency of the cathode materials to spent graphite mass ratios (6,12,18,24,30,36,42, and 48 g g −1 ), ball-to-powder mass ratios (5,10,15,20, and 25 g g −1 ), mill rotation speeds (200, 400, 600, and 800 rpm), and rotation times (2, 4, 6, and 8 h) were investigated systematically. To prevent the equipment from overheating, the ball mill was operated continuously for 10 min with 10 min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…13 However, lithium is generally the last metal recovered through this method, resulting in a serious loss of lithium resources 14 and impurity of the extracted metal salts. In contrast, pyrometallurgical recovery of lithium-ion batteries, which primarily consists of reduction roasting [15][16][17] and molten-salt roasting, [18][19][20][21] mostly converts the LIBs into transition metal oxides and lithium salts that are readily separated. However, the agents used for molten-salt roasting contain sulphur, chlorine, or nitrogen, which produce hazardous gases and waste liquids, 22 and increase the load on subsequent processing.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce energy consumption and increase metal recovery efficiency, some processes combining pyrometallurgy and hydrometallurgy have been widely explored for recycling spent LIBs. Yang et al reported a low-temperature chlorination pyrolysis technology for recycling spent NCM batteries. Similarly, (NH 4 ) 2 SO 4 has also been widely employed in the study of recycling spent LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…24 Gaseous reductants including NH 3 , 25 CH 4 , 26 and H 2 (ref. 27 and 28) have also been explored, and the results were promising in reducing the waste LIB cathodes.…”
Section: Introductionmentioning
confidence: 99%